Development and multicentre validation of a prognostic model to predict resectability of pancreatic head malignancy. Issue 5 (8th June 2018) - Gerken, K; Roberts, K J; Reichert, B; Sutcliffe, R P; Marcon, F; Kamarajah, S K; Kaltenborn, A; Becker, T; Heits, N G; Mirza, D F; Klempnauer, J; Schrem, H
Abstract: Background: At the time of planned pancreatoduodenectomy patients frequently undergo exploratory laparotomy without resection, leading to delayed systemic therapy. This study aimed to develop and validate a prognostic model for the preoperative prediction of resectability of pancreatic head tumours. Methods: This was a retrospective study of patients undergoing attempted resection for confirmed malignant tumours of the pancreatic head in a university hospital in Hannover, Germany. The prognostic value of patient and tumour characteristics was investigated in a multivariable logistic regression model. External validation was performed using data from two other centres. Results: Some 109 patients were included in the development cohort, with 51 and 175 patients in the two validation cohorts. Eighty patients (73·4 per cent) in the development cohort underwent resection, and 37 (73 per cent) and 141 (80·6 per cent) in the validation cohorts. The main reasons for performing no resection in the development cohort were: local invasion of vasculature or arterial abutment (15 patients, 52 per cent), and liver (12, 41 per cent), peritoneal (8, 28 per cent) and aortocaval lymph node (6, 21 per cent) metastases. The final model contained the following variables: time to surgery (odds ratio (OR) 0·99, 95 per cent c.i. 0·98 to 0·99), carbohydrate antigen 19-9 concentration (OR 0·99, 0·99 to 0·99), jaundice (OR 4·45, 1·21 to 16·36) and back pain (OR 0·02, 0·00 to 0·22), with an area under the receiver operating characteristic (ROC) curve (AUROC) of 0·918 in the development cohort. AUROC values were 0·813 and 0·761 in the validation cohorts. The positive predictive value of the final model for prediction of resectability was 98·0 per cent in the development cohort, and 91·7 and 94·7 per cent in the two external validation cohorts. [Corrections added on 18 July 2018, after first online publication: The figures for OR of the variables time to surgery and CA19-9 in the abstract and in Table 3 and Table 4 were amended from 1·00 to 0·99] Conclusion: For preoperative prediction of the likelihood of resectability of pancreatic head tumours, this validated model is a valuable addition to CT findings. Graphical Abstract: In the present study we have developed and successfully validated a prognostic model to predict resectability of pancreatic head malignancy in a national (Kiel, Germany) and international (Birmingham, United Kingdom) patient cohort. The area under the receiver operating characteristic curve (AUROC) in the development cohort was 0·918, in the two validation cohorts 0·813 and 0·761, respectively. The positive predictive value for the prediction of resectability was 98% in the development cohort, 91·7% in the cohort from Kiel and 94·7% in the cohort from Birmingham. Model helps to predict resectability